FGF23 in Cardiovascular Disease: Innocent Bystander or Active Mediator? - Stöhr, Robert; Schuh, Alexander; Heine, Gunnar H.; Brandenburg, Vincent (Frontiers in Endocrinology, 2018)
Fibroblast growth factor – 23 (FGF23) is a mainly osteocytic hormone which increases renal phosphate excretion and reduces calcitriol synthesis. These renal actions are mediated via alpha-klotho as the obligate co-receptor. Beyond these canonical “mineral metabolism” actions, FGF23 has been identified as an independent marker for cardiovascular risk in various patient populations. Previous research has linked elevated FGF23 predominantly to left-ventricular dysfunction and consecutive morbidity and mortality. Moreover, some experimental data suggest FGF23 as a direct and causal stimulator for cardiac hypertrophy via specific myocardial FGF23-receptor activation, independent from alpha-klotho. This hypothesis offers fascinating prospects in terms of therapeutic interventions, specifically in patients with chronic kidney disease in whom the FGF23 system is strongly stimulated and in whom left-ventricular dysfunction is a major disease burden. However, novel data challenges the previous stand-alone hypothesis about a one-way road which guides unidirectionally skeletal FGF23 towards cardiotoxic effects. In fact, recent data point towards local myocardial production and release of FGF23 in cases where (acute) myocardial damage occurs. The effects of this local production and the physiological meaning are under current examination. Moreover, epidemiologic studies suggest that high FGF-23 may follow, rather than induce, myocardial disease in certain conditions. In summary, while FGF23 is an interesting link between mineral metabolism and cardiac function underlining the meaning of the bone-heart axis, more research is needed before therapeutic interventions may be considered.